Faktor Karakteristik Klinis Host dan Sosiodemografik yang Berpengaruh Terhadap Kejadian Dengue Shock Syndrome - Dias Irawan Prasetya; Suharyo Hadisaputro; Muchlis Achsan Udji Sofro; Djoko Trihadi Lukmono; Martini Martini (Jurnal Epidemiologi Kesehatan Komunitas, 2017)
Background : Dengue Shock Syndrome (DSS) is DHF grades III and IV, which can result in disease severity and lead to the death. In 2016, the number of DHF/DSS cases in Semarang City was 2.200 cases (IR=124,50) with 293 cases DSS or 15,4% from DHF, and CFR DSS cases is 9,21%.Methods : An observational analytic was conducted with case-control study design. Study populations were patients with diagnosis of DSS or diagnosis of DHF that admitted inK.R.M.T Wongsonegoro Hospital Semarang City. The samples were 70 cases and 70controls by consecutive sampling. Data were analyzed by logistic regression.Results : Patients DHF with age ≤ 15 years OR=4,277 (95% CI=1,325-13,598), secondary infection OR=2,807 (95% CI=1,116-7,055), hepatomegaly OR=3,206 (95% CI=1,055-9,745) and thrombocytopenia (<50.000/µL) OR=11,301 (95% CI= 4,674-27,325) is a factors that influenced for incidence of dengue shock syndrome. Sex, nausea/vomiting,hemoconcentration, BMI, blood type, prolonged acces to health services, signs of spontaneous bleeding, abdominal pain, hypotension, acces to health services, knowledge and awareness of parents / suffers were not associated with DSS.Conclusion : Host clinical characteristic variables were evident influenced to DSS is age ≤ 15 years, secondary infection, hepatomegaly, and thrombocytopenia (<50.000/µL).